Health-related Quality of Life in Infants With Chronic Liver Disease. Issue 5 (May 2016) - Mohammad, Saeed; Kaurs, Elizabeth; Aguirre, Vincent P.; Varni, James W.; Alonso, Estella M.
ABSTRACT: Objective: The objective of the present study was to report on the health-related quality of life (HRQOL) of infants with chronic liver disease using the PedsQL (Pediatric Quality of Life Inventory) Infant Scales. Methods: The 36-item (ages 1–12 months) and 45-item (ages 13–24 months) PedsQL Infant Scales (physical functioning, physical symptoms, emotional functioning, social functioning, cognitive functioning) were completed by 50 parents of infants with chronic liver disease. Results: Infants ages 1 to 12 months had significantly lower HRQOL scores compared with a matched healthy sample. Infants 13 to 24 months trended to lower physical HRQOL scores that did not reach statistical significance. Recent hospitalizations had an impact on the majority of HRQOL subscales, as did ascites, and failure to thrive. Conclusions: Infants ages 1 to 12 months with chronic liver disease demonstrate lower HRQOL compared with healthy children with physical subscales being most severely affected. The PedsQL Infant Scales allow the definition of HRQOL during a critical period of an infants' development that has been heretofore difficult to measure.